Meningkatkan Hasil Belajar Siswa Kelas IXA SMPK Santa Maria 1 Malang Pada Tema Keluhuran Martabat Manusia Melalui Model Pembelajaran PBL - Simon Petrus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education is a personal relationship between educators and learners. This relationship is referred to as a functional relationship, namely educators as teachers and learners as learning subjects. School is one of the means that can improve the development of students' knowledge. The success of the learning process, especially Catholicism, cannot be separated from the ability of educators to develop learning models that are oriented to increasing the intensity of student involvement effectively in the learning process. The development of the right learning model basically aims to create learning conditions that allow students to learn actively and enjoyably so that students can achieve optimal learning and achievement. Based on existing conditions, teachers can provide learning experiences by designing the learning process. One of the learning models that can be applied is Problem Based Learning (PBL) or problem-based learning. The purpose of this study is to describe the implementation of the Problem Based Learning Model can improve learning outcomes in Class IXA students of SMPK Santa Maria 1 Malang on the Theme of Nobleness of Human Dignity. The type of research carried out is Classroom Action Research (Active Classroom Research). Data Collection Techniques through observations, questionnaires and tests. The data that has been collected is grouped into three types, namely learning management data, student activity data in learning, and student learning outcomes data, and arrive at conclusions by making references to problem formulations. The implementation of learning using the Problem Based Learning (PBL) Learning Model and the Use of the Problem Based Learning (PBL) Learning Model can improve the learning outcomes of Catholic Religious Education in grade IXA students of Santa Maria Catholic Junior High School 1 Malang.